Strategi pengembangan personal branding terhadap seniman lukis independen di Jakarta - Ali, Reynard Jeremy; Widjaja, Indra (Universitas Tarumanagara, 2024)
This research aims to examine branding development strategies for independent painting artists. This research uses a qualitative approach to case studies of several independent painting artists who have successfully built their brand image through effective branding strategies. The data collection method used was in-depth interviews with independent painting artists who were the subjects of the case study. The collected data was then analyzed using qualitative analysis techniques to identify the main themes that emerged from the interviews. The theoretical basis used in this research includes the concepts of personal branding, strategic management, and painting. Relevant previous research is also used as a reference in developing the thinking framework. It is hoped that the results of this research will provide an in-depth understanding of effective branding development strategies for independent painting artists. With this understanding, independent painting artists can improve their personal branding, better market their art, and achieve their goals in the fine arts industry. The researcher sees the fact that the content creation industry on Instagram social media has great opportunities for both artists who have been working for a long time and also those who are just starting as beginners. The researcher believes that through the data described, namely the use of social media, especially Instagram, is the only and best personal branding development strategy at this time for independent painting artists. Penelitian ini bertujuan untuk mengkaji strategi pengembangan citra merek bagi seniman lukis independen. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus terhadap beberapa seniman lukis independen yang berhasil membangun citra merek melalui strategi citra merek yang efektif. Metode pengumpulan data yang digunakan adalah wawancara mendalam terhadap seniman lukis independen yang menjadi subjek studi kasus. Data yang terkumpul kemudian dianalisis dengan menggunakan teknik analisis kualitatif untuk mengidentifikasi tema-tema utama yang muncul dari wawancara. Landasan teori yang digunakan dalam penelitian ini meliputi konsep citra merek, manajemen strategis, dan pengecatan. Penelitian-penelitian terdahulu yang relevan juga dijadikan acuan dalam mengembangkan kerangka berpikir. Hasil penelitian ini diharapkan dapat memberikan pemahaman mendalam mengenai strategi pengembangan citra merek yang efektif bagi seniman lukis independen. Dengan pemahaman ini, seniman lukis independen dapat meningkatkan citra mereknya, memasarkan karya seninya dengan lebih baik, dan mencapai tujuannya di industri seni rupa. Peneliti melihat fakta bahwa industri pembuatan konten di media sosial Instagram mempunyai peluang yang besar baik bagi para seniman yang sudah lama berkarya maupun mereka yang baru memulai sebagai pemula. Peneliti meyakini melalui data yang diuraikan, yaitu penggunaan media sosial, khususnya Instagram, merupakan satu-satunya strategi pengembangan citra merek yang terbaik saat ini bagi seniman lukis independen.